The nexus of biofuels, climate change, and human health : workshop summary - Pool, Robert, 1955- (National Academies Press (US), 2014)
Liquid fuels are a major part of modern life. They supply energy for ground, water, and air transportation as well as power for industrial and farming machinery. But fossil fuels - the dominant liquid fuel in use for well over a century - have many disadvantages. The use of fossil fuels has obvious health downsides, such as emissions of pollutants that are directly harmful to health. The burning of fossil fuels produces greenhouse gases, which contribute to global warming, itself a long-term threat to human health. There have also been health concerns related to insecurity of liquid fuel supplies and the potential of international conflicts being caused by fuel scarcity. Furthermore, there are concerns that the world's large but still limited supply of fossil fuels could be strained by the increasing demand that results from societies around the world achieving greater prosperity. In the face of these concerns, new policies have been created that encourage the development of renewable sources of energy in general and biofuels in particular. In January 2013, the Roundtable on Environmental Health Sciences, Research, and Medicine of the Institute of Medicine held a 2- day, interactive, public workshop on the intersection of biofuels, climate change, and human health. Workshop attendees explored public health issues related to the composition of traditional and alternative fuels and fuel additives, and they discussed the known and potential health impacts associated with the use of these fuels and fuel additives. The Nexus of Biofuels, Climate Change, and Human Health is the summary of that workshop. This report examines air, water, land use, food, and social impacts of biomass feedstock as an energy resource, and the state of the science and health policy implications of using different types (and generations) of biofuels as an energy source.